Why is voluntary co-operation condemned to failure? Reflections on the Polish and German background - Lackowska, Marta (Lex localis, 2009)
This paper investigates the mechanisms that hamper voluntary co-operative arrangements in metropolitan areas. The study on such arrangements in Poland and Germany reveals that the problems related to the self-interests of the metropolitan actors impede stable and effective performance of these initiatives in both national contexts. The analysis has led to the detection of the vicious circle mechanism that is responsible for underperformance. Its main elements are tha lack of appropriate competence and compellability, free-riding among partners, and metropolitan-wide leadership issues. The identified constraints lead to the dilemma between the non-hierarchical co-operative networks and the need for co-ordination mechanisms that are strong enough to enforce long-term non-egoistic actions. The main finding casts doubts ao the non.coercive co-operation treated as a plausible and effective mode of governance in metropolitan regions.
Keywords: javna uprava; Nemčija; Poljska; prostovoljstvo